Breakpoints in ventilation, cerebral and muscle oxygenation, and muscle activity during an incremental cycling exercise - Racinais, Sebastien; Buchheit, Martin; Girard, Olivier (Frontiers in Physiology, 2014)
The aim of this study was to locate the breakpoints of cerebral and muscle oxygenation and muscle electrical activity during a ramp exercise in reference to the first and second ventilatory thresholds. Twenty-five cyclists completed a maximal ramp test on an electromagnetically braked cycle-ergometer with a rate of increment of 25W/min. Expired gazes (breath-by-breath), prefrontal cortex and vastus lateralis (VL) oxygenation (Near-infrared spectroscopy) together with electromyographic Root Mean Square activity for the VL, rectus femoris (RF) and biceps femoris (BF) muscles were continuously assessed. There was a non-linear increase in both cerebral deoxyhemoglobin (at 56±13% of the exercise) and oxyhemoglobin (56±8% of exercise) concomitantly to the first ventilatory threshold (57±6% of exercise, p>0.86, Cohen’s d< 0.1). Cerebral deoxyhemoglobin further increased (87±10% of exercise) while oxyhemoglobin reached a plateau/decreased (86±8% of exercise) after the second ventilatory threshold (81±6% of exercise, p< 0.05, d>0.8). We identified one threshold only for muscle parameters with a non-linear decrease in muscle oxyhemoglobin (78±9% of exercise), attenuation in muscle deoxyhemoglobin (80±8% of exercise), and increase in electromyographic activity of VL (89±5 % of exercise), RF (82±14 % of exercise) and BF (85±9 % of exercise). While the thresholds in muscle oxygenation and RF electromyographic activity were contemporary to V-T2 (d< 0.7), these for BF and VL electromyographic activity occurred after the second ventilatory threshold (p< 0.05, d>0.6). Our results suggest that the metabolic and ventilatory events characterizing this latter cardiopulmonary threshold may affect both cerebral and muscle oxygenation levels, and in turn, muscle recruitment responses.